INDICATORS OF BUSINESS PERFORMANCE: A VIEW FROM THE EXPERTS OF THE FEDERAL FLUMINENSE UNIVERSITY - Rodrigues, Vivian Magalhães; Oliveira, Ualison Rébula (Brazilian Journal of Operations & Production Management, 2015)
During the technological evolution of the means of production and services, indicators of performance were usually used - from the more intuitive to the most elaborate forms - to convey information and support decisions. Verifying the difficulty of Micro and Small Enterprises (MSE) on planning strategies, generating data and implementing information for decision support systems, there is a need to prepare an introductory set of performance indicators for this important kind of organization - as shown in this paper. To achieve this goal, we studied the Balanced Scorecard – a model of performance indicators highly diffused worldwide - to choose the most popular indicators for Micro and Small Enterprises. The main results of this study are fifteen performance indicators targeted in the four perspectives of the Balanced Scorecard, which in the opinion of experts on the subject are ideal for introducing support in decision making for micro and small organizations strategies. In this context, this article aimed to raise the opinion of PhDs from the University Federal Fluminense (UFF), which act in different areas, about the main types of business performance indicators applicable to Micro and Small Enterprises. To accomplish this, a theoretical background was applied on performance indicators and on the Balanced Scorecard model. Besides that, the authors have conducted interviews with doctors of UFF in the areas of financial, customer, internal business process and learning and growth to develop a set of fifteen indexes. These fifteen indicators compose the set of performance indicators for MSE. It was concluded that the objectives were achieved and this study may well contribute to the academic community and to society, as so for businesses by presenting a set of introductory performance indicators for those micro and small companies that don’t have this practice.